Larval production by crossbreeding and artificial insemination of freshwater prawns - Soundarapandian, P; Kannupandi, T (Indian Journal of Fisheries, 2011)
Interspecific crossing has been attempted between Macrobrachium malcolmsonii and M. rosenbergii two cultivable freshwater prawns. The respective females successfully produced viable larvae. The hatching rate and survival percentage increases with increase in size of both the species and it was comparatively higher in M. rosenbergii females. In intraspecific insemination trials, three M. malcolmsonii females produced viable larvae and another three shed their eggs. However, four M. rosenbergii females produced viable larvae and two shed their eggs. In interspecific insemination trials, females shed their eggs after about 6 to 8 days of incubation.